Türkiye’de yatırım ve kalkınma bankacılığı - Küçük, Dilek (My University, 2005)
INVESTMENT AND DEVELOPMENT BANKING IN TURKEY It is impossible to assess investment banks as competitors of development banks in developing countries. In this point, in the developing countries where the capital market is not sufficiently developed, development and investment banks established for the purpose of World Bank support after 1950, have met the middle and long term loan requirements of underdeveloped countries, accelerating their development and contributing to the development of the capital market. In transferring foreign resources to various countries, investment banks and development banks are in an intensive competition, and development banks have transformed into investment banks in the transition process by making multi-purpose development banking in order to meet the requirements. In Turkish banking system, number of banks increased to 48 as of 2005. Number of investment and development banks within the system increased to 13. As of 2003, investment and development banks have a 3% share in the overall banking system based on the size of their assets. 3% of banks not accepting deposits is public capital banks while 8% is private capital and 2% is foreign capital banks. The proportion of Investment and Development Banks in Turkish Banking System is quite low. The main reason is that commercial banks have major shares by employing universal banking strategies and that there is competition. In order to increase the active roles of Investment and Development banks, it is crucial to increase the share provided by financial facilities and it depends on developing the resources of Investment and Development Banks. Improvements in the World Finance System have been in favor of investment banks and it is impossible to maintain their activities of development banks solely by facilitating middle and long-term credits. Therefore, their transformation into investment banks ensure their existence in the future. With this transformation, banks have new resources and resort to increasing the range of their services.

TÜRKİYE'DE YATIRIM VE KALKINMA BANKACILIĞI Gelişmekte olan ülkelerde yatırım bankalarının, kalkınma bankalarının karşısında bir banka olarak değerlendirilmesi imkansızdır Bu noktada sermaye piyasasının yeterince gelişmediği gelişmekte olan ülkelerde, 1950 sonrası Dünya Bankası desteği ile yatırımların finansmanını sağlamak üzere kurulan kalkınma ve yatırım bankaları, azgelişmiş ülkelerin orta ve uzun vadeli kredi ihtiyacını karşılayarak, kalkınmasını hızlandırmış, sermaye piyasasının gelişmesine katkıda bulunmuşlardır. Yurtdışı kaynakların ülkelere transferinde, yatırım bankaları ile kalkınma bankaları yoğun rekabete girmiş ve kalkınma bankaları yoğun rekabette ayakta kalabilmek için çok amaçlı kalkınma bankacılığı yaparak geçiş süreci içinde yatırım bankacılığına dönüşmüşlerdir. Türk Bankacılık Sistemi'nde 2005 yılı itibariyle toplam banka sayısı 48'e yükselmiştir. Sistemde yer alan kalkınma ve yatırım bankalarının sayısı ise 13 olmuştur. 2004 yılı itibariyle kalkınma ve yatırım bankaları, toplam banka sistemi içinde aktif büyüklüklerine göre % 3 paya sahiptir. Mevduat kabul etmeyen bankaların 3'ü kamu sermayeli, 8'i özel sermayeli ve 2'si yabancı sermayeli bankadır. Kalkınma ve yatırım bankalarının Türk bankacılık sistemindeki ağırlıkları son derece azdır. Bunun başlıca nedeni, ticaret bankalarının evrensel bankacılık yaparak sistem içinde büyük bir paya sahip olmaları ve rekabetin ortaya çıkmasıdır. Kalkınma ve Yatırım Bankaları'nin etkinliğini arttırabilmek için, çalıştıkları sektördeki mali faaliyetten aldıkları payın arttırılabilmesi gereklidir. Bu da Kalkınma ve Yatırım Bankaları'nin kaynaklarının geliştirilebilmesine bağlıdır. Dünya finans sistemindeki gelişmeler, yatırım bankacılığı lehine gelişmektedir. Bununla birlikte kalkınma bankalarının sadece orta ve uzun vadeli krediler vererek faaliyetlerini sürdürme imkanı yoktur. Dolayısıyla yatırım bankalarına dönüşmeleri gelecekte ayakta kalmalarını sağlamaktadır. Bu dönüşümle birlikte bankalar, yeni kaynaklara kavuşarak, hizmet çeşitlenmesine gitmektedirler.
Keywords: Ekonomik Gelişim_Türkiye; Kalkınma Bankaları; Yatırım Bankacılığı